Exercising Caution Upon Waking–Can Exercise Reduce Sleep Inertia? - Kovac, Katya; Ferguson, Sally A.; Paterson, Jessica L.; Aisbett, Brad; Hilditch, Cassie J.; Reynolds, Amy C.; Vincent, Grace E. (Frontiers in Physiology, 2020)
Sleep inertia, the transitional state of reduced alertness and impaired cognitive performance upon waking, is a safety risk for on-call personnel who can be required to perform critical tasks soon after waking. Sleep inertia countermeasures have previously been investigated, however none have successfully dissipated sleep inertia within the first 15 min following waking. During this time on-call personnel could already be driving, providing advice, or performing other safety-critical tasks. Exercise has not yet been investigated as a sleep inertia countermeasure but has the potential to stimulate the key physiological mechanisms that occur upon waking, including changes in cerebral blood flow and functional connectivity within the brain, the cortisol awakening response and increases in core body temperature. Here we examine these physiological processes and hypothesises how exercise can stimulate them, positioning exercise as an effective sleep inertia countermeasure. We then propose key considerations for research investigating the efficacy of exercise as a sleep inertia countermeasure, including the need to determine the intensity and duration of exercise required to reduce sleep inertia, as well as testing the effectiveness of exercise across a range of conditions in which the severity of sleep inertia may vary. Finally, practical considerations are identified, including the recommendation that qualitative field-based research be conducted with on-call personnel to determine the potential constraints in utilising exercise as a sleep inertia countermeasure in real-world scenarios.